Explicit leader behaviour preferences: Turkish and cross-national sample comparisons - (:unkn) unknown (Emerald Group Publishing Ltd., 2013)
Purpose: In this study the authors endeavour to further develop and validate the Behavioural and Contingency theory of leadership. Design/methodology/approach: In a field survey research study, the authors collect, analyse, compare, and discuss explicit leader behaviour preferences of employed businesspeople in Istanbul and Izmir, Turkey, rating their "ideal managerial leader" and their actual organisational manager. Findings: In Istanbul and Izmir businesspeople tend to prefer leaders who focus on managing the business system over other considerations such as relationship management; task orientation is more important than relationship orientation. In the business environment, there appear to be little or no differences in preferences relating to gender; men and women have nearly identical preferences; age has some influence; generally, older businesspeople tend to have higher preference scores for a managerial leader who clearly defines his or her own role, and lets followers know what is expected, and pushes them to work harder and exceed past performance. Subordinates neither received nor expected Paternal leader behaviour. They expected and did receive moderately Authoritarian leader behaviour. Originality/value: The large majority of studies of leadership focus on implicit leadership theory, describing characteristics and traits of leaders. This study employs explicit leader behaviour theory and operationalisations to identify subordinates' ideal leader behaviour compared to actual organisational manager behaviour in Turkey. © Emerald Group Publishing Limited.
Keywords: Cross-cultural studies; Explicit leadership theory; Leader behaviour; Leadership; Turkey